Effectiveness of First‐Line Bevacizumab in Metastatic Colorectal Cancer: The Observational Cohort Study GRETA. (10th August 2018) - Franchi, Matteo; Barni, Sandro; Tagliabue, Giovanna; Ricci, Paolo; Mazzucco, Walter; Tumino, Rosario; Caputo, Antonietta; Corrao, Giovanni
Abstract: Background: Scant real‐world data exist on the clinical outcomes associated with the use of bevacizumab‐containing chemotherapy (B+CT) in patients with metastatic colorectal cancer (mCRC). The primary objective of the GRETA cohort study was to compare the overall survival (OS) of patients with mCRC treated with first‐line B+CT versus chemotherapy (CT) alone, in an Italian clinical practice setting. Materials and Methods: Incident patients with mCRC were identified during the period 2010–2012 from five population‐based cancer registries in Italy. Cases were linked to regional health care utilization databases to obtain the entire spectrum of health services provided to each patient. Patients starting a first‐line treatment with B+CT or CT alone within 90 days from the diagnosis were included in the study cohort. A propensity score (PS) method was applied to account for residual confounding. Results: Of 480 patients with mCRC included in the study cohort, 21.0 received first‐line B+CT, and 79.0% received CT. Patients receiving B+CT were younger ( p < .001) and underwent surgery more frequently ( p = .001). The median OS was 22.5 and 14.6 months for B+CT and CT, respectively ( p = .011). The corresponding hazard ratios adjusted by multivariate modeling and PS matched analysis were 0.82 (95% confidence interval [CI], 0.62–1.08) and 0.86 (95% CI, 0.56–1.33), respectively. Similar results were observed after subgrouping by age and surgery. Conclusion: In this Italian real‐world setting of unselected mCRC, the OS of patients treated with B+CT was consistent with previous observational and patient‐registry studies. However, definitive evidence of an improvement in OS cannot be drawn. Abstract : The GRETA study, reported here, was designed to compare the overall survival (OS) of metastatic colorectal cancer patients treated with first‐line bevacizumab‐containing chemotherapy (B+CT) with the OS of those receiving chemotherapy (CT) alone.